THE ROLE OF BEHAVIOR STEREOTYPES IN FORMING OF DIGESTIVE TRACT PATHOLOGY. ANALYSIS OF FEEDING OF SCHOOLCHILDREN IN IVANOVO REGION - E.A. Vishneva; V.V. Omel'yanovskii; E.V. Antonova; T.A. Gavrilova; S.A. Yanovsky; G.G. Shishkareva (Union of pediatricians of Russia, 2008)
There has been noted a significant growth of spread of behavior reactions fraught with health risks among children lately. Peculiarities of behavior stereotypes among children may be a considerable factor, determining functional disorders at first and subsequently more serious pathology conditions. This determined the relevance of large scale complex research on health conditions among teenagers of Ivanovo city and Ivanovo region. The research included the study of school children morbidity, determination of the role of behavior stereotypes in forming of digestive tract pathology, elaboration of possible measures for improvement of cases on gastrointestinal tract diseases.Key words: feeding analysis, addictive behavior, teenage morbidity, forming of digestive tract pathology.